The Structure of Citizen Perceptions of Crime and Disorder: New Insights from a Caribbean Community - Maguire, Edward R. (Journal of quantitative criminology, 2017)
Objectives: This study builds on existing research from US cities on the construct and discriminant validity of perceptual measures of crime and disorder. It seeks to determine whether citizens distinguish between crime and disorder. Methods: This study draws on quantitative and qualitative data from a high-crime community in Trinidad and Tobago, a small-island developing nation in the eastern Caribbean. Analysis of the quantitative data relies on exploratory and confirmatory factor analysis methods designed for use with categorical observed variables and continuous latent variables. Results: In contrast to previous research, we find that citizens do distinguish between physical disorder and general crime, but there is a perceptual overlap for some drug-related offenses and types of social disorder. Conclusions: This study raises questions about the external validity of research on the relationship between perceptions of crime and disorder conducted in the US, and contributes to ongoing discussions and debates about the meaning of disorder. The findings suggest the need for theory and research to explain how context shapes not only the magnitudes of these perceptions, but also their structures. The results also demonstrate the benefits of mixed-methods research approaches in this area of study.